2017
DOI: 10.1007/978-1-4939-6788-9_25
|View full text |Cite
|
Sign up to set email alerts
|

A Histochemical Technique for the Detection of Annonaceous Acetogenins

Abstract: Annonaceous acetogenins (ACGs) are molecules with carbon numbers C35-C37, usually with tetrahydrofuran and tetrahydropyran rings and one terminal γ-lactone (usually α,β-unsaturated), in a large aliphatic chain that is varyingly hydroxylated, acetoxylated or ketonized. ACGs have ecological functions as insecticides and are pharmacologically promising due to their cytotoxic and antitumoral properties. They are found in the seeds, leaves, roots, flowers and fruits of annonaceous plants and can be detected during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Annona squamosa Leaves, tender stem, Bark, Seeds, Stem bark. Anonaine,Anolobine,Aporphine,Corydine,Isocorydine,Norcorydine,Norisocorydine, Glaucine,Liriodenine,Norlaureline,Norushinsunine,Reticuline,Roemerine,Samoquasine A, Annosqualine,Cyclosqamosin A, Cyclosqamosin B, Cyclosqamosin C, Cyclosqamosin D, Cyclosqamosin E, Cyclosqamosin F, Cyclosqamosin G, Cyclosqamosin H, Cyclosqamosin I, Squamtin A, Annosquamosin A, Annonacin, AnnonacinA, Annonastatin, Squamocin, Squamocin-O1, Squamocin-O2, Bullatacin, Bullatacinone, 4-deoxyannoreticuin, cis-4deoxyannoreticuin(2,4-cis and trans)-squamoxinone, (2,4-cis and trans)-Mosinone A, Mosin B, Mosin C, Squamotacin, Molvizarin, (2,4-cis and trans)-squamolinone, (2,4-cis and trans)-9-oxoasimicinone, Bullacin B, Squamostatin D, (2,4-cis-and trans)-bullatacinone, Squamostatin C, Annonin I, Annonin VI, Squamostene-A, Reticulacin-1, Squamosinin-A, Annotemoyin-1, Annotemoyin-2, Annomosin A, Annosquamosins A,Annosquamosins B, Annosquamosin C, Annosquamosin D, Annosquamosin E, Annosquamosin F, Annosquamosin G.[36]Annona macroprophyllataSeedsLaherradurin; rolliniastin-2; cherimolin-2[37] Annona muricata Annonaine, nornuciferine, asimilobine, epomusenin-A, epomusenin-B, epomurinin-A, epomurinin-B, cis-annoreticuin, muricin J, muricin K, muricin L, cinnamic acid derivative, coumaric acid hexose, 5-caffeoylquinic acid, dihydrokaempferol-hexoside, p-coumaric acid, caffeic acid derivative, e, dicaffeoylquinic acid, feruloylglycoside, 4-feruloyl-5-caffeoylquinic acid, p-coumaric acid methyl ester,annomuricin A, annomuricin B, annomuricin C, annomuricin E, annomutacin, (2,4-cis)-10R-annonacin-A-one, (2,4-trans)-10Rannonacin-A-one, annohexocin, muricapentocin, (2,4-cis)-isoannonacin, (2,4-trans)-isoannonacin, muricatocin A, muricatocin B, muricatocin C, gigantetronenin,annopentocin A, annopentocin B,annopentocin C, cisannomuricin-D-one, trans-annomuricin-D-one,murihexocin A, murihexocin B, murihexocin C ,muricoreacin, Cis-corossolone, annocatalin, annocatacin B, anonaine, isolaureline, xylopine,Quercetin 3-O-α-rhamnosyl-(1→6)-βsophoroside, gallic acid,epicatechine, quercetin 3-O-rutinosid, quercetin 3-O, neohispredoside, quercetin 3-O-robinoside, catechine, chlorogenic acid, argentinine (1-N,Ndimethylethanyl-4,6-dimethoxy-3,8-dihydroxy-phenanthrene), kaempferol 3-O-rutinoside, quercetin 3-O-glucoside, quercetin, kaempferol, annonamine, (S)-norcorydine, (R)-4′-Omethylcoclaurine (R)-O,O-dimethylcoclaurine, ,annoionol A, annoionol B, annoionol C, annoionoside,, vomifoliol, roseoside,turpinionoside A,citroside A, blumenol C, (+)-epiloliolide, loliolide, ,rutin, kaempferol 3-O-rutinoside, kaempferol 3-O-robinobioside, kaempferol 3-O-β-D-(2′ ′-O-β-D-glucopyranosyl,6′′-O-α-L-rhamnopyranosylglucopyranoside, montecristin, cohibin A, cohibin B, cis-solamin, cis-panatellin,cis-uvariamicin IV, cis-uvariamicin I, cis-reticulatacin, cis-reticulatacin-10-one, chatenaytrienin 1, chatenaytrienin 2, chatenaytrienin 3, muridienin 3, muridienin 4, muricadienin, coronin, sabadelin, murisolin, muricatacin, donhexocin, cohibin C, cohibin D, muricatenol, 2,4-cis-gigantetrocinone, 2,4-trans-gigantetrocinone, 2,4-trans-isoannonacin-10-one, annomontacin, longifolicin,muricin A, muricin B, muricin C, muricin D,muricin E,muricin F, muricin G, muricin H, muricin I, cisannomontacin, annonacinone, xylomaticin, N-fatty acyl tryptamines, annoreticuin-9-one, epoxymurin A epoxymurin B, corepoxylone, annonacin-10-one, isoannonacin, isoannonacin-10-one, goniothalamicin, gigantetrocin, gigantetrocin A gigantetrocin B, muricatetrocin A, muricatetrocin B,epomuricenin A epomuricenin B, annomuricatin A, annocatacin A, annomuricatin C, annonacin [38] Annona reticulata Leaf, Bark, Stem bark, Root, Root bark, Seed, Fruit Dopamine, Salsolinol, Coclaurine, Sesquiterpenes mainly Spathenelol, Muurolene, Copaene, Eudesmol, Acetogenin -Squamone, Solamin, Annomonicin, Rolliniastatin 2, Annoreticuin-9-one. Triterpenoidannonaretin A, Monotetrahydrofuron acetogenins, Ret...…”
mentioning
confidence: 99%
“…Annona squamosa Leaves, tender stem, Bark, Seeds, Stem bark. Anonaine,Anolobine,Aporphine,Corydine,Isocorydine,Norcorydine,Norisocorydine, Glaucine,Liriodenine,Norlaureline,Norushinsunine,Reticuline,Roemerine,Samoquasine A, Annosqualine,Cyclosqamosin A, Cyclosqamosin B, Cyclosqamosin C, Cyclosqamosin D, Cyclosqamosin E, Cyclosqamosin F, Cyclosqamosin G, Cyclosqamosin H, Cyclosqamosin I, Squamtin A, Annosquamosin A, Annonacin, AnnonacinA, Annonastatin, Squamocin, Squamocin-O1, Squamocin-O2, Bullatacin, Bullatacinone, 4-deoxyannoreticuin, cis-4deoxyannoreticuin(2,4-cis and trans)-squamoxinone, (2,4-cis and trans)-Mosinone A, Mosin B, Mosin C, Squamotacin, Molvizarin, (2,4-cis and trans)-squamolinone, (2,4-cis and trans)-9-oxoasimicinone, Bullacin B, Squamostatin D, (2,4-cis-and trans)-bullatacinone, Squamostatin C, Annonin I, Annonin VI, Squamostene-A, Reticulacin-1, Squamosinin-A, Annotemoyin-1, Annotemoyin-2, Annomosin A, Annosquamosins A,Annosquamosins B, Annosquamosin C, Annosquamosin D, Annosquamosin E, Annosquamosin F, Annosquamosin G.[36]Annona macroprophyllataSeedsLaherradurin; rolliniastin-2; cherimolin-2[37] Annona muricata Annonaine, nornuciferine, asimilobine, epomusenin-A, epomusenin-B, epomurinin-A, epomurinin-B, cis-annoreticuin, muricin J, muricin K, muricin L, cinnamic acid derivative, coumaric acid hexose, 5-caffeoylquinic acid, dihydrokaempferol-hexoside, p-coumaric acid, caffeic acid derivative, e, dicaffeoylquinic acid, feruloylglycoside, 4-feruloyl-5-caffeoylquinic acid, p-coumaric acid methyl ester,annomuricin A, annomuricin B, annomuricin C, annomuricin E, annomutacin, (2,4-cis)-10R-annonacin-A-one, (2,4-trans)-10Rannonacin-A-one, annohexocin, muricapentocin, (2,4-cis)-isoannonacin, (2,4-trans)-isoannonacin, muricatocin A, muricatocin B, muricatocin C, gigantetronenin,annopentocin A, annopentocin B,annopentocin C, cisannomuricin-D-one, trans-annomuricin-D-one,murihexocin A, murihexocin B, murihexocin C ,muricoreacin, Cis-corossolone, annocatalin, annocatacin B, anonaine, isolaureline, xylopine,Quercetin 3-O-α-rhamnosyl-(1→6)-βsophoroside, gallic acid,epicatechine, quercetin 3-O-rutinosid, quercetin 3-O, neohispredoside, quercetin 3-O-robinoside, catechine, chlorogenic acid, argentinine (1-N,Ndimethylethanyl-4,6-dimethoxy-3,8-dihydroxy-phenanthrene), kaempferol 3-O-rutinoside, quercetin 3-O-glucoside, quercetin, kaempferol, annonamine, (S)-norcorydine, (R)-4′-Omethylcoclaurine (R)-O,O-dimethylcoclaurine, ,annoionol A, annoionol B, annoionol C, annoionoside,, vomifoliol, roseoside,turpinionoside A,citroside A, blumenol C, (+)-epiloliolide, loliolide, ,rutin, kaempferol 3-O-rutinoside, kaempferol 3-O-robinobioside, kaempferol 3-O-β-D-(2′ ′-O-β-D-glucopyranosyl,6′′-O-α-L-rhamnopyranosylglucopyranoside, montecristin, cohibin A, cohibin B, cis-solamin, cis-panatellin,cis-uvariamicin IV, cis-uvariamicin I, cis-reticulatacin, cis-reticulatacin-10-one, chatenaytrienin 1, chatenaytrienin 2, chatenaytrienin 3, muridienin 3, muridienin 4, muricadienin, coronin, sabadelin, murisolin, muricatacin, donhexocin, cohibin C, cohibin D, muricatenol, 2,4-cis-gigantetrocinone, 2,4-trans-gigantetrocinone, 2,4-trans-isoannonacin-10-one, annomontacin, longifolicin,muricin A, muricin B, muricin C, muricin D,muricin E,muricin F, muricin G, muricin H, muricin I, cisannomontacin, annonacinone, xylomaticin, N-fatty acyl tryptamines, annoreticuin-9-one, epoxymurin A epoxymurin B, corepoxylone, annonacin-10-one, isoannonacin, isoannonacin-10-one, goniothalamicin, gigantetrocin, gigantetrocin A gigantetrocin B, muricatetrocin A, muricatetrocin B,epomuricenin A epomuricenin B, annomuricatin A, annocatacin A, annomuricatin C, annonacin [38] Annona reticulata Leaf, Bark, Stem bark, Root, Root bark, Seed, Fruit Dopamine, Salsolinol, Coclaurine, Sesquiterpenes mainly Spathenelol, Muurolene, Copaene, Eudesmol, Acetogenin -Squamone, Solamin, Annomonicin, Rolliniastatin 2, Annoreticuin-9-one. Triterpenoidannonaretin A, Monotetrahydrofuron acetogenins, Ret...…”
mentioning
confidence: 99%
“…Table 2 and Table 3 show some phytochemicals (quantitative or qualitative) identified in pulp, leaf, peel, seeds, roots, and stem bark of fruit Annona species: A. muricata, A. cherimola, A. squamosa, A. reticulata, and A. macroprophyllata [ 83 , 84 , 85 , 86 , 87 , 88 , 89 ]. These compounds include phenolic compounds, alkaloids, fatty acids, cyclopeptides, alkaloids, and acetogenins.…”
Section: Agronomic Knowledgementioning
confidence: 99%
“…In the seeds of some Annona species bioactive compounds named cyclopeptides have been reported that in recent years have been of much pharmaceutical interest. Annomuricin A-C has been extracted and identified from A. muricata seeds ( Table 3 ) [ 89 , 101 , 102 ]. Two other cyclopeptides (cherimolacyclopeptide E and F) were obtained from A. cherimola seeds [ 103 , 104 ].…”
Section: Agronomic Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Annonaceous acetogenins are mainly extracted from seeds of Annonaceae plants [13], and ASSO is separated during the extraction process, which is generally discarded. However, it has been reported that Annona squamosa seed oil (ASSO) has anti-oxidant activity [14], anti-psoriatic activity [15], lipoxygenase inhibitory activity [16], and antitumor activity.…”
Section: Introductionmentioning
confidence: 99%